Mental Accounting Practices and Spending Behavior of Collegiate Students at National University Baliwag: An Assessment - Jovette Torres; Eilysea Geronimo; Elijah Marie Estabas; Nicole Banquerigo; Elijah Fritz Buenaflor; Jhon Carlo Serapio; Fideliz Arca Vidal (SEISENSE Business Review)
This study assesses the influence of mental accounting practices on the spending behavior of college students at National University Baliwag. It aims to understand how gender and school affiliation influence these connections. The research employs a combination of applied, quantitative, explanatory, and descriptive methods, utilizing data collected through a three-sectioned questionnaire from a sample of 361 students. The findings revealed a high negative correlation between mental accounting practices and spending behavior, stating that students who utilize mental accounting tend to have controlled spending habits. Furthermore, it was noted that gender has no significant difference in mental accounting practices but has a difference in spending behavior. The School of Engineering, Architecture, and Technology (SEAT) showed the highest mental accounting practices, while the School of Tourism and Hospitality Management (STHM) had the highest spending behavior. While several studies have linked mental accounting practices in various shopping methods, this research contributes to the literature by applying the mental accounting theory within a university context in the Philippines. This study is important in understanding behavioral finance, providing guidance and practical implications for the beneficiaries of the study.